2015
DOI: 10.1093/cercor/bhv017
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Direct Encoding of Numerosity in the Visual Stream

Abstract: Humans are endowed with an intuitive number sense that allows us to perceive and estimate numerosity without relying on language. It is controversial, however, as to whether there is a neural mechanism for direct perception of numerosity or whether numerosity is perceived indirectly via other perceptual properties. In this study, we used a novel regression-based analytic method, which allowed an assessment of the unique contributions of visual properties, including numerosity, to explain visual evoked potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

36
201
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(261 citation statements)
references
References 50 publications
(62 reference statements)
36
201
8
1
Order By: Relevance
“…Therefore, the rTPJ may reflect a pattern of asymmetric automatic processing of numerical and nonnumerical magnitudes. These results appear to contradict the findings of Park et al (Park, DeWind, Woldorff, & Brannon, 2015). This study used the temporal resolution of an EEG and found that, during passive viewing of dot arrays, response to numerical magnitudes occurred earlier than response to nonnumerical magnitudes and that the brain was more sensitive to changes in numerical than in nonnumerical magnitudes.…”
Section: Discussioncontrasting
confidence: 75%
“…Therefore, the rTPJ may reflect a pattern of asymmetric automatic processing of numerical and nonnumerical magnitudes. These results appear to contradict the findings of Park et al (Park, DeWind, Woldorff, & Brannon, 2015). This study used the temporal resolution of an EEG and found that, during passive viewing of dot arrays, response to numerical magnitudes occurred earlier than response to nonnumerical magnitudes and that the brain was more sensitive to changes in numerical than in nonnumerical magnitudes.…”
Section: Discussioncontrasting
confidence: 75%
“…Recent electroencephalogram (EEG) studies have found modulation of the ERP signal specific to changes in numerosity early in the time course along sites in the visual cortex for nonsymbolic number processing (even when accounting for visual properties of the stimuli;Fornaciai & Park, 2017;Park, Dewind, Woldorff, & Brannon, 2016). Thus, the clusters found in the visual cortex align with recent evidence suggesting that the visual cortex is uniquely sensitive to nonsymbolic numerical representations.In light of the present findings, it would be of value in future research to explore the role of the IPS in different types of computa-tions.…”
supporting
confidence: 59%
“…In these areas 57 electrophysiological recordings in monkeys identified single neurons tuned to specific 58 numerosities of visual arrays (Nieder et al, 2002;Nieder and Miller, 2004;Roitman et al, 59 While these earlier findings mostly pointed at the key role of parietal and frontal areas in 73 numerical representation, some recent studies found that it is possible to decode the number 74 of items seen by the subjects from the fMRI activity patterns in early visual areas (Bulthé et 75 al., 2014;Eger et al, 2015;Bulthé et al, 2015;DeWind et al, 2018, but see Castaldi et al, 76 2016). Moreover, spatially organized numerosity maps were recently claimed to extend to the 77 occipital cortex (Harvey and Dumoulin, 2017a) and early ERP components compatible with 78 generators in early visual areas responded to variations in the numerosity of visual arrays 79 (Park et al, 2015;. 80…”
mentioning
confidence: 99%
“…For what concerns the neuronal level, a few recent 110 studies have started to directly quantify the effects of non-numerical dimensions of non-111 symbolic numerical stimuli (e.g. Park et al, 2015;Harvey and 112 Dumoulin, 2017b; Fornaciai and Park, 2018;DeWind et al, 2018). Those studies found that 113 activity in earlier (occipital) or later (parietal) brain regions appeared to be linked to the 114 numerical content of sets after taking into account effects of certain non-numerical 115 dimensions.…”
mentioning
confidence: 99%